Relevance of Cloud Computing and its Significance: Addressing Challenges and Developing Algorithms for a Secure and Scalable Real-Time Banking System using Cloud Computing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cloud computing is an emerging paradigm of computing in which computing infrastructure resources are provided as internet services. Cloud computing allows consumers and businesses to use applications without installation and to access their personal files on any computer with internet access. As promising as it is, this paradigm also presents many new challenges to data security and access control when users outsource sensitive data to cloud servers that are not within the same trusted domain as data owners. Cryptographic methods are used to keep sensitive user data confidential against unreliable servers by disclosing data decryption keys to authorized users only. This thesis explores the secure and scalable real-time banking system operating model using cloud computing. Cloud computing has the potential for tremendous benefits, but wide-scale adoption has a number of challenges that need to be addressed. These challenges have been reviewed and how they relate to computing. This thesis is therefore capable of achieving a secure and scalable real-time banking system operating model using cloud computing by developing and applying new generated algorithms.